The effect of topical ciprofloxacin and steroid-containing ear drops for chronic suppurative otitis media on the internal ear - Kapusuz, Zeliha; Keles, Erol; Alpay, Hayrettin Cengiz; Karlidag, Turgut; Kaygusuz, Irfan; Uzunlar, Ali Kemal; Yalcin, Sinasi (Springer, 2010)
Aim of the study is to evaluate the effects of topical ciprofloxacin and prednisolone-containing ear drops for chronic suppurative otitis media on hearing threshold, cochlear reserve and cochlea morphology in healthy subjects and to determine the proper drug dose. Sixty-eight guinea pigs, all of which had healthy hearing, were used for the study. The first group (n = 30) was administered ciprofloxacin three times a day, the second group (n = 30) was administered prednisolone three times a day and the third group (n = 8) was administered sterile distilled water three times a day. The therapies lasted for 7 days and were administered intratympanically. The first group and second group were divided into three sub-groups of ten subjects. The first sub-group (n = 10) was administered an equivalent dose per kilogram as in humans, the second sub-group (n = 10) was administered one-third of the human-equivalent dose and the third sub-group (n = 10) was administered tenfold the human-equivalent dose. All subjects underwent brainstem evoked response audiometry (BERA) and distortion product otoacoustic emission (DPOAE) testing on the seventh and twenty-first days following the therapy. Following the tests, two subjects from each group were decapitated and examined under electron microscope. BERA and DPOAE testing results of the sub-group (n = 10) which was administered tenfold the human-equivalent dose were significantly different from the control group and other groups (P < 0.05). According to electron microscopic examination of the cochlea, the group which was administered a tenfold human-equivalent dose of intratympanic ciprofloxacin and prednisolone showed atrophy in cells and degenerations in cilia. This case was statistically significant when compared with the control group and other groups (P < 0.05). Ciprofloxacin and prednisolone applied at a human-equivalent dose per kilogram did not affect the hearing and cochlear histology of subjects.
Keywords: Ciprofloxacin; Prednisolone; Ototoxicity